Behavior Based Work Family Conflict, Age, and Tenure as Antecedents of Organizational Commitment: A Study of Policewomen - Bakar, Resekiani; Rahmat, Muhammad Aulia; Anwar, Hilwa (Polteknik Ilmu Pemasyarakatan, 2025)
The limited number of police women in Indonesia poses a challenge not only to the implementation of security in society but also to the problem of organizational commitment due to work-family conflicts that occur from the dual role of being a policewoman and being responsible at home. This study examines the effect of work-family conflict and personal factors (age and tenure) on the organizational commitment of women police officers. This study also analyzes the aspect of work-family conflict, which significantly increases the organizational commitment of women police officers. The study's respondents were 80 policewomen in one of the Metropolitan Police Station (Polrestabes) areas in Indonesia who were married and had children. Data collection used self-reporting in the form of a work-family conflict scale and an organizational commitment scale. Regression test analysis shows a negative effect of work-family conflict on organizational commitment. Behavior-based conflict is a substantial aspect for police women in increasing organizational commitment. This research has implications for the police institution in creating a working system that can balance work and family for a positive organizational.